Quality of Service (QoS) in Virtual Private Network (VPN) - A Study on standard and Non-standard VPN Protocols. - Kedah, Mohd Rosli (universiti teknologi petronas, 2005)
VPNs are a must for all organizations planning to compare in the global competitive marketplace. To put this remarkable solution to effective use, network administrator and othe IT professionals (students) must have an in-depth knowledge of all technologies related to VPNs and their implementation. It has been implemented in most of well known companies such as JARING in Malaysia. With this, it is very potential to increase the used of it among Universities and also medium companies. This paper presents the proposed topic on the Virtual Private Network using standard and non standard protocol which are PPTP and cIPe protocol using Fedora Core operating system. The main objective is to generate general awareness to the public and students concerning the security of data shared within the public network generally through Internet and especially within intranet. This due to several security problems occurs and for the cost effectiveness implementation of the network itself The knowledge in networking using LINUX also gives advantage for IT Professionals to compete in job market. The scope of study will focus two different protocols which divided into standard which is Point To Point Tunneling protocol (PPTP) and also the Crypto IP Encapsulation protocol (cIPe) which cover up the importance of data sharing issues nowadays. The project will implement several research and information gathering/study and the methods used are field experiment which considered on System Development Life Cycle (SDLC) and the used of latest version of LINUX Operating System, Fedora Core 3. The results expected would be the working Virtual Private Network among the different protocols itself and also on how the protocols operated in satisfying the importance of these VPN technology approaches. The final work can then be used as good reference to students who are deep interested in networking area or Linux operating system and also for further understanding about the Quality of Service in Virtual Private Network